مركزية مقاصد الشريعة في تنزيل الأحكام على القضايا المعاصرة - Refki Saputra (Al-Zahra : Journal for Islamic and Arabic Studies, 2022)
Contemporary life is witnessing rapid change and tremendous development in all aspects in which number of matters, incidents and cases have appeared requiring scholars to explain on their legal description and the legal rules. This research attempts to clarify the status of the main purposes of Sharia and its pivotal authority in the process of creating Sharia rules on an incident. The research revealed the role of the purposes of Sharia in the particular ijtihad in order to ensure the fulfillment of the intended goals by the God because the process of creating the rules pays attention on achieving the purposes, public goods, and goals sought by the Sharia by legislating those rules. The research employed the inductive and analytical approach, based on approved references and sources. The research concludes that the purposes of Sharia have a major central role in the process of creating a rule on an incident. This central role is represented in five basic matters: in realizing the basis of the rule, in changing the rule in order to change its area, in postponing the application of the rule in urgent circumstances, in excluding an incident from the general rule, and in favoring a jurisprudential opinion that is appropriate to the place of judgment and achieves the intended interests of the Sharia.